STUDENT GROUP AS A FACTOR IN THE FORMATION OF STUDENTS' EDUCATIONAL AND PROFESSIONAL ATTITUDES - VASYLENKO, Olena; MARTYNIUK, Inna (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2025)
The article describes the peculiarities of the influence of the student group on the formation of students' educational and professional attitudes. It has been found that the formation of students' learning motivation and educational and professional attitudes largely depends on the level of development of the group to which they belong. It has been established that in the student's age there is an active formation of the personality of the future specialist and a significant role in this is played not only by the content of education, but also by the student environment, that is, the student group, which has a socialising and educational effect on the student's personality. A student group is a primary, small group officially established in a higher education institution, which is determined by the needs of management. It has been emphasised that the nature of the development and acquisition of professional competences by a student largely depends on the level of development of the student group to which he or she belongs. It is found that the higher the level of development of the group, the stronger its influence on the individual student. It is established that the knowledge-based approach, which is based on the need to provide students with only professional knowledge and the formation of their skills and abilities, leads to a certain neglect of the problem of the formation of the personality of a specialist within a student group, and does not pay due attention to the development of their professional potential and the formation of educational and professional attitudes. It has been found that an attitude is a state of readiness, a predisposition of an individual to a certain activity or action in a certain situation, determined by past experience. It performs a variety of functions, the main ones being: the function of the nature of the course of stable activity, which allows maintaining its focus in rapidly changing situations; the function of freeing a person from the need to make decisions and control the course of activity in standard situations; the function of inertia of activity, which makes it difficult to adapt to new situations. Educational and professional attitudes are defined as an effective factor in the formation of a future specialist, so the formation of educational and professional attitudes is an important factor that ensures the development of his or her personal qualities and moral values. It is established that interaction in a student group determines the paradigm of professional communication of students and is a factor in the formation of their educational and professional attitudes. It is proposed to use the potential of student groups and active teaching methods in the development of students' learning motivation and educational and professional attitudes.